PENGARUH PROFITABILITAS, LEVERAGE, MARKET ACTIVITY, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENGUNGKAPAN INTERNET FINANCIAL REPORTING - Dewi Latifah; Dina Anggraeni Susesti (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
Internet financial reportinng is a term used to describe financial and non-financial reporting carries out online. The company’s ability to increase the timely publication of financial information through internet financial reporting can be done with the fundamental management of profitability, leverage, market activity, and size of the company. The purpose of this study is to find empirical evidence and analyze the effec of profiability, leverage, market activity, and company size on internet financial reporting (in food and beverage industry manufacturinng companies listed on the IDX in 2017-2021). This research is a quantitative study using logistic regression analysis and hypothesis testing with the help of the SPSS V.26 software application with a significance level of 0.05. The sampling method used purposive sampling and obtained 27 companies with a total sample of 135 financial reports as research objects. The resuls of this study indicate that profitability has a significan positive effect on internet financial reporting. Leverage has a negative and insignificant effect on Internet financial reporting. Market activity has a significant positive effect on Internet Fiinancial Reporting. Company size has a significant positive effect on Internet Financial Reporting.